Amyand’s hernia complicated with perforated appendicitis in neonates: a case report - Kamarul Zaman, Nabila Yuliyanty; Ab. Rahman, Norhafiza; Lechmiannandan, Abhirrami; Othman, Mohd Yusran; Abdullah, Mohd Yusof (2022)
Introduction: Inguinal hernia (IH) is a common condition encountered in premature neonates. Amyand’s hernia (AH) is an uncommon form of IH in which the hernia sac contains appendix. Surgical repair of AH is similar to usual IH, however if it contains a perforated and inflammed appendix, the diagnosis and repair can be challenging.